ECN+: A marking-aware optimization for ECN threshold via per-Port in Data Center Networks. (15th February 2020) - Majidi, Akbar; Jahanbakhsh, Nazila; Gao, Xiaofeng; Zheng, Jiaqi; Chen, Guihai
Abstract: Explicit Congestion Notification (ECN) is a powerful tool for quality of service in single queue scenarios. However, the industry trends to have Multi-Queue (MQ) per-port in Data Center Networks (DCNs). Having an MQ per-port is harmful at least for a scheduling policy of ECN. For instance, all the packets could get ECN marking due to the buffer pressure of the other queues belonging to the same shared port. By seeking solutions to the problems mentioned above, we propose a marking-aware optimization for ECN threshold via per-port marking in DCNs (ECN + ). The intuition is that if any packet gets marked in the MQ buffer, ECN + will not consider them in the marking decision of the Output Port Buffer (OPB). Furthermore, we show how this ignoring keeps the queue occupancy and ECN marking threshold ( K ) lower to achieve low latency. We do so through theoretical analysis of marked packets ratio in MQ and subtracting it from OPB. Besides, we calculate the ratio of the marked packet in OPB to achieve the minimum and maximum queue oscillations so that we can find an optimal K . To the best of our knowledge, we are the first to discuss the problem of faulty ECN marking via OPB through the fraction of marked packets. Steady-state analysis and simulation results demonstrate that ECN + utilizes the buffer capacity, exactly 30% to absorb micro-burst traffic without sacrificing the latency.